2013
DOI: 10.1785/0120120253
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic Tremor beneath Cuba Triggered by theMw 8.8 Maule andMw 9.0 Tohoku‐Oki Earthquakes

Abstract: We provide additional evidence of tectonic tremor in Cuba triggered by the 2010 M w 8.8 Maule, Chile, and the 2011 M w 9.0 Tohoku-Oki, Japan, earthquakes. The high-frequency tremor signals are modulated by long-period surface waves, similar to triggered tremors observed in other tectonically active regions. We are able to locate two tremor sources triggered by the Tohoku-Oki earthquake near the east-west trending Oriente fault around Guantanamo Bay. The tremor around Guantanamo Bay was triggered primarily by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…The large stars show the study regions of triggered tremor following the 2011 M w 9.0 Tohoku, Japan, earthquake. The small stars mark the newly identified regions with triggered tremor reported by recent studies (e.g., Rubinstein et al, 2011;Gonzalez-Huizar et al, 2012;Peng et al, 2012;Zigone et al, 2012;Aiken et al, 2013). Regions where episodic tremor and slowslip events have been observed are marked as squares.…”
Section: °60°ementioning
confidence: 86%
See 3 more Smart Citations
“…The large stars show the study regions of triggered tremor following the 2011 M w 9.0 Tohoku, Japan, earthquake. The small stars mark the newly identified regions with triggered tremor reported by recent studies (e.g., Rubinstein et al, 2011;Gonzalez-Huizar et al, 2012;Peng et al, 2012;Zigone et al, 2012;Aiken et al, 2013). Regions where episodic tremor and slowslip events have been observed are marked as squares.…”
Section: °60°ementioning
confidence: 86%
“…In addition, we also include several regions where ambient or triggered tremor have been found in previous studies, but no triggered tremor occurred during the Tohoku mainshock (i.e., the CF in northern California and Guerrero in Mexico) and in regions where the Tohoku mainshock triggered tremor, but were not analyzed in this study (i.e., Cuba;Gonzalez-Huizar et al, 2012;Peng et al, 2013). We sort these regions according to their distances relative to the epicenter of the Tohoku mainshock.…”
Section: Triggered Tremor Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, recent studies have shown that triggered tremor does occur in transpressive environments, such as major strike-slip faults near plate boundaries (e.g., Peng et al, 2009;Shelly et al, 2011;Aiken et al, 2013;Peng et al, 2013). Gomberg et al (2012) conducted an initial search of ambient tremor in the aftershock zone of the 2002 Denali fault earthquake without success.…”
Section: Introductionmentioning
confidence: 99%